Mechanism of hyperbaric oxygen therapy downregulating H-type angiogenesis in subchondral bone of knee osteoarthritis through the PHD2/HIF-1α pathway - Jianjian Wang; Wen Yu; Yuxin Zhang; Bo Chen; Zhaoxiang Meng (Journal of Orthopaedic Surgery and Research)
Abstract Objective To explore the mechanism of hyperbaric oxygen therapy in inhibiting subchondral bone angiogenesis and delaying the progression of osteoarthritis through the PHD2/HIF-1α signaling pathway. Methods Mice were randomly divided into three groups (control group, osteoarthritis group, and hyperbaric oxygen treatment group). The effect of hyperbaric oxygen therapy on osteoarthritis was evaluated using Micro-CT, Safranin O-Fast Green staining, and detection of osteoarthritis inflammation markers (MMP-13, ADAMTS-5, Col2a1, and Aggrecan). The activation relationship between PHD2 and downstream signaling pathways was investigated through gene knockout and overexpression experiments. Finally, cell scratch assays, tube formation assays, and chondrogenic differentiation experiments were conducted to verify the mechanism of the PHD2/HIF-1α signaling pathway under hyperbaric oxygen stimulation. Results Hyperbaric oxygen therapy delayed the progression of osteoarthritis in mice. It promoted chondrogenic differentiation of mesenchymal stem cells, inhibited angiogenesis, enhanced PHD2 expression, and suppressed the production of HIF-1α and VEGFA. Silencing/overexpression of PHD2 resulted in increased/decreased production of HIF-1α and VEGFA, respectively. Conclusion The hyperbaric oxygen environment promotes the expression of PHD2, accelerates the degradation of HIF-1α, and inhibits the production of VEGFA, thereby reducing the generation of type H vessels in subchondral bone.